2021
DOI: 10.1101/2021.08.04.455042
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

But Mouse, you are not alone: On some severe acute respiratory syndrome coronavirus 2 variants infecting mice

Abstract: In silico predictions combined with in vitro, in vivo and in situ observations collectively suggest that mouse adaptation of the SARS-CoV-2 virus requires an aromatic substitution in position 501 or position 498 (but not both) of the spike protein receptor binding domain. This effect could be enhanced by mutations in positions 417, 484 and 493 (especially K417N, E484K, Q493K and Q493R), and to a lesser extent by mutations in positions 486 and 499 (such as F486L and P499T). Such enhancements due to more favoura… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The RBDs of alpha, beta and gamma variants have been shown to bind murine ACE2 with higher affinity than RBD of the wt/D614G strain [18]. This increased binding can be explained by in silico predictions based on comparative structural analysis of different VOC RBDs towards N501Y mutation as key in enhanced mACE2 recognition [19]. The combination of this in silico information with the results of the experimental work from our group and others [20] strongly suggests common mice (Mus musculus) as another animal species susceptible to SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RBDs of alpha, beta and gamma variants have been shown to bind murine ACE2 with higher affinity than RBD of the wt/D614G strain [18]. This increased binding can be explained by in silico predictions based on comparative structural analysis of different VOC RBDs towards N501Y mutation as key in enhanced mACE2 recognition [19]. The combination of this in silico information with the results of the experimental work from our group and others [20] strongly suggests common mice (Mus musculus) as another animal species susceptible to SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, the occurrence of mouse-to-mouse transmission remains to be studied experimentally, as well as whether the now globally dominant delta variant would possess the ability to infect mice. However, the lack of N501Y or other mutations associated with increased mACE2 affinity suggest this would be unlikely [19].…”
Section: Discussionmentioning
confidence: 99%
“…Most B.1.1.529 isolates have a constellation of changes in the spike protein including: A67V, D69-70, T95I, G142D, D143-145, D211, L212I, insertion 214EPE, G339D, S371L, S373P, S375F, K417N, N440K, G446S, S477N, T478K, E484A, Q493R, G496S, Q498R, N501Y, Y505H, T547K, D614G, H655Y, N679K, P681H, N764K, D796Y, N856K, Q954H, N969K, and L981F. The presence of the N501Y mutation along with additional mutations (K417, E484, Q493, Q498, and N501) at sites associated with mouse adaptation by serial passage [23][24][25][26][27][28] suggested that B.1.1.529 should infect laboratory strains of mice 29 . Indeed, one recent study speculated that because mutations in the B.1.1.529 spike protein overlap with ones known to promote adaptation to mouse hosts, the progenitor of B.1.1.529 jumped from humans to mice, and then back into humans 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Several prevalent mutations have been identified in the receptor-binding domain (RBD) of the spike protein ( 4 , 5 ), which may extend the host range or switch host tropism. Previous studies showed that N501Y alone ( 6 , 7 ) or in combination with K417N/T and E484K enhanced the affinities to mouse ( 4 , 7 9 ) and rat ACE2 proteins ( 10 ) and conferred the SARS-CoV-2 variants the ability to infect mouse cell lines ( 6 , 11 ). Furthermore, Xavier Montagutelli et al.…”
Section: Introductionmentioning
confidence: 99%